2012
DOI: 10.1007/s10147-012-0392-x
|View full text |Cite
|
Sign up to set email alerts
|

Attributes of brain metastases from breast and lung cancer

Abstract: Brain metastases from lung occur earlier, are more edematous, but fewer in number than those from breast cancers. Cerebellar brain metastases are more frequent in breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 21 publications
1
18
1
1
Order By: Relevance
“…As reported previously, there were no significant differences in the size of BM between several primary tumors [2][3][4].…”
Section: Introductionsupporting
confidence: 68%
See 1 more Smart Citation
“…As reported previously, there were no significant differences in the size of BM between several primary tumors [2][3][4].…”
Section: Introductionsupporting
confidence: 68%
“…Imaging findings, especially magnetic resonance imaging (MRI) features of BM have been described in detail previously [2][3][4]. According to the literature, BM from different primary tumors also showed different MRI patterns [2,3].…”
Section: Introductionmentioning
confidence: 96%
“…Metastases have more distinct borders in comparison to gliomas, and may have surrounding vasogenic edema that is disproportionate to the size of the lesion. 90 Cerebellar involvement is more common in breast cancer, and lung cancer is generally associated with larger amounts of surrounding vasogenic edema when compared with breast cancer. 90 Melanoma has unique imaging features that may be highly suggestive of the diagnosis.…”
Section: Tumormentioning
confidence: 99%
“…90 Cerebellar involvement is more common in breast cancer, and lung cancer is generally associated with larger amounts of surrounding vasogenic edema when compared with breast cancer. 90 Melanoma has unique imaging features that may be highly suggestive of the diagnosis. Non-hemorrhagic melanoma may appear hyperintense on T1-weighted images and isointense to hypointense on T2-weighted images sec-ondary to the intrinsic paramagnetic effects of melanin pigment.…”
Section: Tumormentioning
confidence: 99%
“…Hengel et al reported that BM from lung cancer are more likely to show an edema at >3–4 cm in diameter compared to BM from breast cancer, but the size above which a BM initiates VE formation has not been further studied [14]. Since we demonstrated that the general minimum cut-off value for the presence of VE is a BM diameter of 9.4 mm, but differs between primary sites, we hypothesize that the above-mentioned mechanisms leading to an edema are histology-specific.…”
Section: Discussionmentioning
confidence: 99%